Cardiac impairments in postacute COVID‐19 with sustained symptoms: A review of the literature and proof of concept. Issue 16 (22nd August 2022) - Singh, Jyotpal; Bhagaloo, Lanishen; Sy, Eric; Lavoie, Andrea J.; Dehghani, Payam; Bardutz, Holly A.; Mang, Cameron S.; Buttigieg, Josef; Neary, J. Patrick
Abstract: Although acute COVID‐19 is known to cause cardiac damage in some cases, there is still much to learn about the duration and relative permanence of the damage that may occur. Long COVID is a condition that can occur when COVID‐19 symptoms remain in the postviral acute period. Varying accounts of long COVID have been described across the literature, however, cardiac impairments are sustained in many individuals and cardiovascular assessment is now considered to be an expected follow‐up examination. The purpose of this review and proof of concept is to summarize the current research related to the assessment of cardiac function, including echocardiography and blood biomarker data, during the follow‐up period in patients who recovered from COVID‐19. Following a literature review, it was found that right ventricular dysfunction along with global longitudinal strain and diastolic dysfunction are common findings. Finally, more severe acute myocardial injury during the index hospitalization appears to exacerbate cardiac function. The available literature implies that cardiac function must be monitored in patients recovered from COVID‐19 who remain symptomatic and that the impairments and severity vary from person‐to‐person. The proof‐of‐concept analysis of patients with cardiac disease and respiratory disease in comparison to those with sustained symptoms from COVID‐19 suggests elevated systolic time interval in those with sustained symptoms from COVID‐19, thus reducing heart performance indices. Future research must consider the details of cardiac complications during the acute infection period and relate this to the cardiac function in patients with long COVID during mid‐ and long‐term follow‐up. Abstract : Cardiac parameters are shown to be impaired in follow‐up research on patients recovered from COVID‐19. Sustained symptoms are not always present with the associated cardiac impairments.